Title: Some principles in doing autoethnography - Elizabeth (Dr), Ho Kam Kau; (Dr) Honorary, Ki Wing Wah (IJRDO-Journal of Applied Science, 2017)
Autoethnography is a popular research method in the understanding of livedexperience in relation with cultural, social and emotional conditions. The paperis going to present a method of doing ‘autoethnography’ with reflective thinkingin which 1. the author is a main participant 2. Use layers of reflective thinking 3.Devote to the understanding of culture and emotion in relation of teaching ethnicminority in the learning of Chinese in his or her life situation. At different stagesof our life, there are episodes of life experience, which we would like to learnfrom it and invite others to share. Writing autoethnography is simply apromising way to help us learn from our lived experience. To achieve thispurpose, an example of teacher’s autoethnography will be reviewed. It is about the emotional challenge experience of a teacher who begins to teach ethnicminority students the dominant language of Chinese in Hong Kong.